Discrete time adaptive reaching law speed control of electrical drives - Akpolat, ZH; Gokbulut, M (Springer-Verlag, 2003)
This paper describes an adaptive control scheme for servomotor speed control systems under inertial and frictional variations. The control is based on reaching law control (RLC), which is an approach to sliding mode control (SMC) design. The adaptations of the control parameters are performed using the gradient descent method. Discrete time implementation of the SMC strategy is considered in the paper, since it is more appropriate for practical applications. It is shown that the robustness of the SMC method is constrained by sampling time. Also shown is the deterioration of the speed responses under the plant parameter variations due to finite sampling time. Thus, an adaptation mechanism for the control parameters is introduced in order to provide a robust control performance under the plant parameter variations. Practical implementation of the proposed control scheme is also discussed in the paper.
Keywords: drive control; sliding mode control; reaching law control; adaptive speed control